Collagen remodeling markers show differentiated expression in patients with ST- and non-ST elevation myocardial infarction. (25th November 2020) - Holm Nielsen, S; Shami, A; Jonasson, L; Swahn, E; Auf Dem Keller, U; Genovese, F; Karsdal, M; Grufman, H; Yndigegn, T; Schiopu, A; Nilsson, J; Edsfeldt, A; et al.
Abstract: Background: Following acute myocardial infarction (MI), the left ventricle undergoes molecular and extracellular matrix (ECM) changes. The ECM is a dynamic structure with a potential role in cardiac remodeling post-MI. Collagens are the major components of both cardiac and arterial ECM. Purpose: We evaluated circulating levels of type I, IV and VI collagen fragments in two cohorts of patients with acute MI to investigate collagen turnover post-MI. The cohorts were Malmö AMI in elderly (MAMI-Y) and Assessing Platelet Activity in Coronary Heart Disease (APACHE). Methods: Serum was collected from 190 patients from the discovery cohort (MAMI-Y: mean age 74, SD 10.8) at four timepoints: admission when MI, after 3–6 days, 6 weeks, 12 months; citrate plasma was collected from 142 patients from the validation cohort (APACHE: mean age 65, SD 11.6) at four timepoints: hospitalization, 3 days, 7–9 days, 6 months. The biomarkers of matrix metalloproteinase (MMP)-mediated degradation of type I collagen (C1M), MMP-mediated degradation of type IV collagen (C4M) and formation of type VI collagen (PRO-C6) were measured at all timepoints (immunosorbent assays). Differences in the markers at the different timepoints were calculated using repeated measures ANOVA. Results: Circulating levels of the formation biomarker PRO-C6 significantly increased from baseline and remained high at all three following timepoints in both MAMI-Y and APACHE studies (all p<0.001). In contrast, the degradation biomarkers C1M and C4M showed a similar pattern of an initial increase 3 days post-MI followed by a decrease over time, with C1M in MAMI-Y and both C1M and C4M in APACHE having returned to baseline level by the final timepoint. Circulating baseline levels of PRO-C6 correlated with age (r=0.397, p<0.0001 in MAMI-Y, r=0.427, p<0.0001 in APACHE). Categorizing the subjects into ST elevation MI (STEMI; MAMI-Y: N=67, APACHE: N=71) or non-ST elevation MI (NSTEMI; MAMI-Y: N=130, APACHE: N=52) revealed that a correlation with age remained in both subgroups (r=0.443, p<0.0001 and r=0.325, p<0.0001, respectively, in MAMI-Y, and r=0.516, p<0.0001 and r=0.316, p=0.023, respectively, in APACHE). Moreover, PRO-C6 was elevated in STEMI patients that had previously experienced an MI in both cohorts (MAMI-Y: p=0.017, APACHE: p=0.016). C1M and C4M levels were not different in patients with prior MI in any of the cohorts. No association was found between any biomarker and gender or diabetes. Echocardiography showed a correlation between baseline levels of C1M and ejection fraction (r=0.228, p=0.023) in the whole MAMI-Y cohort and among NSTEMI, but not among STEMI, subjects (r=0.337, p=0.004). Conclusions: We observed changes in circulating fragments reflecting collagen turnover in the acute phase post-MI, more pronounced in STEMI patients. This may indicate that STEMI patients have more active collagen remodeling than NSTEMI patients and may have more altered left ventricle function and remodeling. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): This work was supported by the Danish Research Foundation "den danske forskningsfond", the Innovation foundation (Innovationsfonden), Swedish Research Council, Swedish Heart and Lung Foundation, Swedish Society for Medical Research, Swedish Society of Medicine, the Crafoord Foundation, the Åke Wiberg foundation and the Stroke foundation.